Impact study of agricultural value added on foreign direct investment, economic development, trade openness for India following ARDL approach - Jekka Chandrasekaran Sharmiladevi (Cogent Economics & Finance, 2023)
This research aims to identify the impact of agriculture, forest and fishing value-added on international business, capital flow, and economic growth for India from 2000 to 2022, by examining short-term and long-term equilibrium using the Auto Regressive Distributive lag (ARDL) approach. Agriculture value added is taken as a dependent variable, and inward Foreign Direct Investment (FDI), stock of net FDI, economic growth and trade openness are taken as independent variables. Results indicate that there exists a long-term and short-term relationship between agriculture value added, economic growth and trade openness. Economic growth and trade openness have a statistically significant relationship with agricultural value added in the short and long run. Inward FDI and stock of FDI are not significant to agriculture value added. ARDL Bound test results indicate that there is a long-term cointegrating relation among the variables. The error correction term is also strong and significant (−13.96), suggesting resistance to shocks. Existing literatures coverage on agriculture and international business is scarce in the Indian context, and this research will be significant in that line. The results of this study resonate with the findings of a few studies conducted in other geographical areas, indicating the fact that the receptivity and absorptive capacity prevailing in an economy play a dominant role in receiving maximum benefits from inward capital flow leading to economic growth. This research reinstates that agriculture still influences economic growth in India. Openness is essential for creating a conducive atmosphere for economic development. The study also indicates the direction for future research.
Keywords: F14; F63; 330; agriculture value added; economic growth; foreign direct investment; trade openness